Sputtered Phosphorus‐Doped poly‐Si on Oxide Contacts for Screen‐Printed Si Solar Cells. Issue 9 (3rd July 2022) - Nasebandt, Lasse; Min, Byungsul; Hollemann, Christina; Hübner, Simon; Dippell, Torsten; Peibst, Robby; Brendel, Rolf
Abstract : The impact of the phosphorus doping density in direct current‐sputtered polysilicon layers on surface passivation and contact resistance by fabricating polysilicon on oxide (POLO) contacts is studied, when applying doping densities ranging from 3 × 10 19 to 4 × 10 20 cm −3 . Hydrogenation is performed either via a hydrogen‐releasing AlO x layer and postdeposition anneals in forming gas using a tube furnace at 400 °C, or by rapid firing of an AlO x /SiN y stack in a conveyor belt furnace at 810 °C. The study shows that the forming gas anneal of the weakly in situ phosphorus‐doped poly‐Si layers with AlO x enables a passivation quality with an implied open‐circuit voltage of up to 734 mV and a recombination current density down to 1.8 fA cm − 2 . For fast firing, a high phosphorus concentration of 4 × 10 20 cm −3 is required for comparably high passivation quality with a recombination current density down to 1.3 fA cm − 2 . A p‐type POLO back‐junction solar cell featuring such ex situ doped sputtered POLO contacts with a cell efficiency of 22.4% and an open‐circuit voltage of 714 mV is fabricated. To our knowledge, this is the highest open‐circuit voltage published so far with sputtered POLO contacts. Abstract : The impact of phosphorus doping densities in sputtered polysilicon layers on surface passivation is studied. Record implied open‐circuit voltages of 734 mV and recombination current densities down to 1.3 fA cm − 2 are achieved. On p‐type polysilicon on oxide back‐junction solar cell featuring ex situ doped sputtered polysilicon, a cell efficiency of 22.4% and an open‐circuit voltage of 714 mV are independently confirmed.